Design of cysteine-S-sulfonated keratin via pH driven processes: Micro-Structural Properties, biocidal activity and in vitro validation. (5th May 2022) - Sanchez Ramirez, Diego O.; Tonetti, Cinzia; Cruz-Maya, Iriczalli; Guarino, Vincenzo; Peila, Roberta; Carletto, Riccardo A.; Varesano, Alessio; Vineis, Claudia
Graphical abstract: Highlights: Keratin-ligand complexes were produced by pH variation. Biocidal activity of protonated keratin against S. aureus was demonstrated. Keratin-lyophilized powder with better thermostability was obtained. Keratin-secondary structures influenced notably cell-material interactions. Abstract: Cysteine-S-sulfonated keratin, protein extracted from wool fibers by sulfitolysis, is a natural polyelectrolyte typically used in biomedical materials like scaffolds and smart biointerfaces. In order to extend and tune its properties, a study of the content of secondary structures, thermostability, biocidal activity and in vitro tests of cell viability on lyophilized cysteine-S-sulfonated keratin were carried out as a function of the pH solution (after keratin extraction and before purification). The results offer considerable evidence of the formation of protein–ligand complexes due to the protonation of keratin, with the presence of bisulfite, citrate, formate and acetate ions. These interactions modify the content of secondary structures in cysteine-S-sulfonated keratin, increase its thermostability (∼50 °C), enhance the stability of positive charges that confers its biocidal activity (pHsolution  < 5.2) and change the interaction between cysteine-S-sulfonated keratin and human mesenchymal stem cells. Lastly, in vitro and antibacterial tests confirm that pH changes may also influence cell and bacteria response, in terms of proliferation, due to the changes of protein secondary structure and positive/negative charges. These results give relevant insights into the process of tuning keratin properties for biomedical applications – i.e., drug delivery, wound healing.